Development and validation of an LC-MS/MS method for the analysis of L-DOPA in oat - Varga, Erika; Varga, Mónika (Acta Biologica Szegediensis, 2014)
L-DOPA (L-3,4-dihydroxyphenylalanine), currently the most effective known therapeutic agent for the symptomatic relief of Parkinson’s disease, is one of the highly active allelochemicals that inhibit the growth and development of certain plant species. A tropical legume, Mucuna pruriens, has been shown to contain from 2 to 7% L-DOPA. However, little is known about the L-DOPA contents of other plants. The aim of our work was to develop and validate a simple method for the LC-MS/MS determination of L-DOPA in different oat varieties. During the development of the method, various LC and MS parameters were optimized from the aspect of sensitivity. In the final method, the calibration curve was linear over the concentration range 10-10,000 pg/μl. L-DOPA could be detected at 18 μg/kg level through use of the [(M+H)-NH3]+ fragment of the [M+H]+ molecular ion. The intraday precision and accuracy were all within acceptable ranges.